1988
DOI: 10.1007/bf00027403
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an isolated transcription stimulating sequence derived from the cauliflower mosaic virus 35S promoter

Abstract: As a highly active plant viral promoter that is able to function in a wide variety of cell types, the cauliflower mosaic virus (CaMV) 35S promoter has the potential for harboring a plant enhancer element. We tested this possibility and demonstrated that a 338 base pair fragment isolated from the region upstream of the 35S TATA box can increase the expression of a low-activity heterologous promoter up to the level observed for the intact 35S promoter. This fragment is fully active in both orientations when plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 24 publications
1
45
0
1
Order By: Relevance
“…Ow et al (1987) reported that, in carrot protoplasts, the -89 5' deletion mutant has 23% WT activity, whereas the -68 5' deletion mutant has only 0.8%. Odell et al (1988) found that deletion of the sequence between -90 and -55 reduces transient expression levels of the -392 to -90 fragment by twofold. We have confirmed and extended these results in transgenic tobacco plants.…”
Section: The -90 To -46 Region Plays An Accessory Role In Transcriptionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ow et al (1987) reported that, in carrot protoplasts, the -89 5' deletion mutant has 23% WT activity, whereas the -68 5' deletion mutant has only 0.8%. Odell et al (1988) found that deletion of the sequence between -90 and -55 reduces transient expression levels of the -392 to -90 fragment by twofold. We have confirmed and extended these results in transgenic tobacco plants.…”
Section: The -90 To -46 Region Plays An Accessory Role In Transcriptionmentioning
confidence: 97%
“…Thus, CaMV fragments containing 400 to 1000 base pairs of 35S upstream sequences have been shown to be active when integrated into the nuclear genome of transgenic tobacco (Odell et al, , 1987Nagy et al, 1987;Kay et al, 1987;Jefferson et al, 1987) and petunia (Sanders et al, 1987). Moreover, the promoter can also be expressed transiently in protoplasts of several dicots and monocots (On-Lee et al, 1986;Fromm et al, 1985;Ow et al, 1987;Nagata et al, 1987;Odell et al, 1988). Quantitative measurements of relative transcript levels in transformed tobacco cells Nagy et al, 1985) or transgenic petunia plants (Sanders et al, 1987) showed that the 35S promoter is at least 30 times stronger than the nopaline synthase promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this strategy is often problematic due to the positionand orientation-independent ability of enhancers to trigger enhancer-promoter interference and disturb the expression of the transgene of interest. This phenomenon is particularly prevalent in transgenic plants harboring constructs in which the enhancer from the CaMV 35S promoter (Odell et al 1988) is in relatively close proximity to the promoter of another transgene, and results in both a loss of specificity and an increase in the level of expression induced by the transgenic promoter Zheng et al 2007). Interestingly, this enhancer-mediated activation of proximal promoters appears to be a fairly common property of a wide range of enhancers, and as a result, has incited interest in the development of strategies with which to prevent such interactions (Gudynaite-Savitch et al 2009;Singer et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…The enhancer-like element (Ϫ351 to Ϫ84) of the CaMV35S promoter (Odell et al 1988) was prepared by PCR from pBI221 with primers 35S-Sal (5Ј-CGTCGACAGGGCAATTGAGAC-3Ј) and 35S-Hind (5Ј-TCAAGCTTTGGAGATATCACATC-3Ј). The PCR cycle conditions were 30 s at 98°C, 30 s at 55°C, and 30 s at 72°C, for 25 cycles.…”
mentioning
confidence: 99%